Скважинный источник импульсов с динамическим пакером - Крауиньш П. Я. Петр Янович; Смайлов С. А. Садык Арифович; Иоппа А. В. Александр Валентинович; Мойзес Б. Б. Борис Борисович; Гаврилин А. Н. Алексей Николаевич; Плотников Е. Г.
опубл. 20.11.01